2020
DOI: 10.1111/are.14894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium butyrate stimulation on immune‐related mRNA‐miRNA network in intestine of grass carp

Abstract: Butyrate has been widely used in animal feeding as one of the most important dietary additives. Sodium butyrate, as the main form for butyrate additive, is popular in farming of animals such as pigs (Biagi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Sodium butyrate (NaBT) is a butyric acid salt formed after the mineralization of BTA by mineral sodium (Abdel-Latif et al, 2020). Several studies showed that dietary BTA and its salts can improve physiological responses (e.g., growth performance, intestinal microflora, antioxidant status, and immunity) in different fish species such as Nile tilapia, Oreochromis niloticus (El-Sayed Ali et al, 2018;Dawood et al, 2020); grass carp, Ctenopharyngodon idella (Liu et al, 2017;Tang et al, 2021); rainbow trout, Oncorhynchus mykiss (Gao et al, 2011;Mirghaed et al, 2019;Sahin et al, 2021;Lin et al, 2023;Liu et al, 2023); turbot, Scophthalmus maximus (Liu et al, 2019); sturgeon, Acipenser baerii (Najdegerami et al, 2015); rice field eel, Monopterus albus (Zhang et al, 2020); Oreochromis niloticus, (Abdel-Latif et al, 2021); goldfish Carassius auratus (Mehrgan et al, 2022); and largemouth bass, Micropterus salmoides (Chen et al, 2023).…”
mentioning
confidence: 99%
“…Sodium butyrate (NaBT) is a butyric acid salt formed after the mineralization of BTA by mineral sodium (Abdel-Latif et al, 2020). Several studies showed that dietary BTA and its salts can improve physiological responses (e.g., growth performance, intestinal microflora, antioxidant status, and immunity) in different fish species such as Nile tilapia, Oreochromis niloticus (El-Sayed Ali et al, 2018;Dawood et al, 2020); grass carp, Ctenopharyngodon idella (Liu et al, 2017;Tang et al, 2021); rainbow trout, Oncorhynchus mykiss (Gao et al, 2011;Mirghaed et al, 2019;Sahin et al, 2021;Lin et al, 2023;Liu et al, 2023); turbot, Scophthalmus maximus (Liu et al, 2019); sturgeon, Acipenser baerii (Najdegerami et al, 2015); rice field eel, Monopterus albus (Zhang et al, 2020); Oreochromis niloticus, (Abdel-Latif et al, 2021); goldfish Carassius auratus (Mehrgan et al, 2022); and largemouth bass, Micropterus salmoides (Chen et al, 2023).…”
mentioning
confidence: 99%